Self-repairing and self-adhesion nano-composite hydrogel material as well as preparation method and application thereof
By introducing boric acid derivative modified monomers and conductive nanofillers into flexible wearable hydrogels, a reversible dynamic polymer network is formed, and the existing hydrogel sensors are solved in terms of mechanical strength, sensing performance and self-repair performance. The shortcomings of the body achieve efficient monitoring of human movement and electrophysiological signal.
Patent Information
- Application Number
- CN202310962593.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-02
- Publication Date
- 2025-02-14
AI Technical Summary
The existing flexible wearable hydrogel-based sensors cannot effectively integrate high sensitivity, high mechanical strength, self-repair performance and self-adhesive performance, limiting their application in the field of wearable sensors.
The mixture of the first monomer, the second monomer and the conductive filler is modified by using boric acid derivatives to form a dynamic polymer network structure through reversible interaction, which improves the mechanical strength and self-healing performance of the hydrogel, and introduces conductive nanofillers. To enhance conductivity and sensing performance.
The high mechanical strength, sensitive sensing performance, reliable self-repair and self-adhesion properties of hydrogel materials are achieved, making them suitable for the application of flexible wearable sensors and can sensitively monitor human motion signals and electrophysiological signals.
Smart Images

Figure CN119431902A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of hydrogel materials, and in particular relates to a self-repairing self-adhesive nano composite hydrogel material and a preparation method and application thereof. Background Art
[0002] With the development of artificial intelligence technology and wearable electronics, traditional rigid sensor devices cannot meet people's needs for wearing comfort and sensing sensitivity. Therefore, it is urgent to develop flexible materials with modulus close to that of human tissue for wearable sensors. As a three-dimensional polymer network structure material that can retain a large amount of water, hydrogel has become one of the ideal materials for preparing flexible wearable sensors due to its high water content, skin-like flexibility and good biocompatibility. However, in practical applications, problems such as low mechanical strength, poor conductivity and sensing performance, easy damage and poor adhesion of hydrogels have limited their development and use as a matrix material for flexible wearable sensors.
[0003] To solve the above problems, Chinese patent CN114149595A discloses a double-network high-elastic hydrogel sensor with an interpenetrating structure and a preparation method thereof, wherein the first monomer (sodium alginate, chitosan, gelatin, carrageenan and curdlan gum) and the second monomer (acrylamide, acrylic acid, isopropyl acrylamide and acrylamide methyl propane sulfonic acid) are cross-linked by physical and chemical methods respectively to form an interpenetrating network structure, which effectively improves the mechanical strength of the hydrogel-based sensor. However, the sensing performance of the hydrogel-based sensor is poor, and it does not have rapid self-repairing and reliable self-adhesion properties. Chinese patent CN114854047A also discloses a double-network conductive hydrogel and a preparation method thereof, wherein the first network is a network formed by chemical crosslinking of acrylamide derivatives, and the second network is a physical crosslinking network formed by the interaction of chitosan derivatives and phytic acid, wherein the free hydrogen ions released by phytic acid effectively improve the conductivity of the hydrogel, and the introduction of chitosan also gives the hydrogel adhesion properties, but once the wearable electronic device assembled by the hydrogel is destroyed in practical applications, the chemical crosslinking network cannot recover by itself, and the only non-covalent effect in the physical crosslinking network cannot make the hydrogel quickly restore its initial performance; more importantly, the sensing sensitivity of this type of hydrogel system is low, and the actual conductivity and sensing performance are difficult to meet the needs of flexible wearable sensors to sensitively collect multi-scale human motion signals or electrophysiological signals. Therefore, it is of great significance to prepare a hydrogel material with high mechanical strength, sensitive sensing performance, reliable self-repair and self-adhesion properties for the development of flexible wearable sensors. Summary of the invention
[0004] In view of the problem that existing flexible wearable hydrogel-based sensors cannot well integrate high sensitivity, high mechanical strength, effective self-repairing performance and reliable self-adhesion performance, the present invention provides a self-repairing and self-adhesive nanocomposite hydrogel material.
[0005] One of the purposes of the present invention is to provide a self-repairing and self-adhesive nanocomposite hydrogel material, comprising a mixture and / or a reaction product of a first monomer modified by a boric acid derivative, a second monomer, and a conductive filler.
[0006] In the self-repairing self-adhesive nanocomposite hydrogel material provided by the present invention:
[0007] The first monomer in the boric acid derivative modified first monomer is selected from at least one of sodium alginate, chondroitin sulfate, sodium hyaluronate, carboxymethyl cellulose and glycyrrhizic acid;
[0008] The boric acid derivative in the first monomer modified by the boric acid derivative is selected from at least one of inorganic boric acid derivatives and organic boric acid derivatives, preferably at least one of borax, boric acid, 3-aminophenylboronic acid and 3-carboxyphenylboronic acid;
[0009] The second monomer is selected from at least one of acrylamide, dopamine, chitosan, carboxymethyl chitosan, gelatin, guar gum, and polyvinyl alcohol;
[0010] The conductive filler is selected from at least one of MXene, carbon black, carbon nanotubes, graphene, reduced graphene oxide, molybdenum disulfide, tungsten disulfide, black phosphorus, liquid metal particles, metal nanoparticles, conductive graphite, and silver nanowires;
[0011] The particle size of the conductive filler is 1 nm to 150 μm, preferably 50 nm to 3 μm.
[0012] The conductive fillers used in the present invention can be prepared by commercially available products or by the preparation methods in the prior art. For example, MXene nanosheets can be prepared by the following method: lithium fluoride is added to hydrochloric acid and stirred evenly, and then Ti3AlC2 is added and stirred to obtain an acidic solution, which is washed and dried to obtain a multi-layer MXene powder; after the powder is dispersed evenly in deionized water, the upper layer of liquid is taken by ultrasonication and centrifugation to obtain the MXene nanosheet solution; wherein the mass ratio of lithium fluoride, inorganic acid, and Ti3AlC2 is 1:(2-8):(1-2); the inorganic acid is selected from at least one of hydrochloric acid and hydrofluoric acid; the stirring conditions are 30-40°C and 20-50h; the washing conditions are washing with deionized water until the solution pH is 6-7; the drying conditions are freeze-drying at -50--20°C; and the dispersion conditions are ultrasonic dispersion under inert gas protection for 1-2h.
[0013] In the self-repairing self-adhesive nanocomposite hydrogel material provided by the present invention,
[0014] Taking the total mass of the first monomer, the second monomer and the conductive filler modified by the boric acid derivative as 100%, the first monomer modified by the boric acid derivative is 1-85%, the second monomer is 15-98%, and the conductive filler is 0.1-10%; preferably, taking the total mass of the first monomer, the second monomer and the conductive filler modified by the boric acid derivative as 100%, the first monomer modified by the boric acid derivative is 3-75%, the second monomer is 20-93%, and the conductive filler is 0.3-8%.
[0015] The second object of the present invention is to provide a method for preparing the self-repairing self-adhesive nanocomposite hydrogel material, comprising: mixing components including the first monomer modified by the boric acid derivative, the second monomer and the conductive filler, and stirring the reaction to obtain the self-repairing self-adhesive nanocomposite hydrogel material. Preferably, the preparation method specifically comprises the following steps:
[0016] Step 1, preparing a dispersion of a conductive filler;
[0017] Step 2: adding a boric acid derivative and a reaction additive to the aqueous solution of the first monomer, stirring and reacting, to obtain a first monomer modified with a boric acid derivative;
[0018] Step 3: Mix the first monomer modified by the boric acid derivative, the second monomer and the conductive filler dispersion, and stir to react to obtain the self-repairing and self-adhesive nanocomposite hydrogel material.
[0019] Preparation method of the self-repairing self-adhesive nanocomposite hydrogel material:
[0020] In the step 1, the solvent in the conductive filler dispersion is water; the concentration of the conductive filler dispersion is 1 to 10 mg / mL, preferably 3 to 6 mg / mL;
[0021] In the step 2, the concentration of the first monomer aqueous solution is 0.01-45wt%, preferably 0.5-30wt%; the reaction additive is selected from at least one of sodium periodate, ethylene glycol, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and N-hydroxysuccinimide; the mass ratio of the first monomer, the boric acid derivative, and the reaction additive is 1:(0.1-1):(0.2-2), preferably 1:(0.2-0.8):(0.3-1.5); the reaction conditions are 0-40°C for 0.5-72h, preferably 4-35°C for 4-48h.
[0022] After the stirring reaction in step 2, purification treatment is required, wherein the purification treatment can adopt the purification process commonly used in the art, such as pouring the solution obtained after the stirring reaction into a dialysis bag, dialyzing with deionized water, and freeze-drying the dialysate to obtain the self-repairing and self-adhesive nanocomposite hydrogel material.
[0023] In the preparation method of the self-repairing self-adhesive nanocomposite hydrogel material, the step three comprises the following steps: adding the first monomer and the second monomer modified by the boric acid derivative to the conductive filler dispersion respectively, stirring and reacting sufficiently to obtain the self-repairing self-adhesive nanocomposite hydrogel material; or, adding the first monomer and the second monomer modified by the boric acid derivative to the conductive filler dispersion in sequence, optionally adding an initiator and a cross-linking agent, stirring and reacting sufficiently to obtain the self-repairing self-adhesive nanocomposite hydrogel material. Wherein, the initiator is selected from at least one of a peroxide initiator and an azo initiator, preferably azobisisobutylimidazoline hydrochloride initiator (AIBI), ammonium persulfate ((NH4)2S2O8), potassium persulfate (K2S2O8), benzoyl peroxide (C 14 H 10 O4); the cross-linking agent is selected from at least one of 6,6'-bisamino-3,3'-methylenedibenzoic acid cross-linking agent (MBAA), N,N'-methylenebisacrylamide (N,N'-Methylenebisacrylamide), tannic acid (TA), catechol (TP), tea polyphenols, Tris-HCl buffer solution, and NaOH; the amounts of the initiator and the cross-linking agent are not particularly limited and can be added according to the amounts commonly used in the art.
[0024] The third object of the present invention is to provide the above self-repairing self-adhesive nanocomposite hydrogel material or the self-repairing self-adhesive nanocomposite hydrogel material obtained by the above preparation method, and its application in flexible wearable sensors and pressure detection sensors. The sensor can be used as a sensing element of wearable flexible devices, and its application is not limited to human motion detection, intelligent medical diagnosis, human-computer interaction perception, intelligent electronic skin, wound dressing, cervical pressure detection, intracranial pressure detection, wound pressure detection and other fields.
[0025] The present invention provides a self-repairing and self-adhesive nanocomposite hydrogel material based on reversible interaction, which comprises a first monomer, a second monomer and a conductive nanofiller. The polymer network formed by the two monomers generates cross-linking through reversible interaction to improve the mechanical strength of the hydrogel, while giving the hydrogel reliable self-repairing performance; in addition, the polymer chain of the hydrogel contains a large number of free active groups, which can achieve adhesion to materials such as skin through reversible interactions between the groups. The incorporation of conductive nanofillers is also beneficial to improving the mechanical properties, conductive properties and sensing properties of the hydrogel, so that the flexible wearable sensor assembled therefrom can sensitively and stably monitor human motion signals and electrophysiological signals.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The present invention provides a self-repairing, self-adhesive nanocomposite hydrogel material based on reversible interactions and a preparation method thereof. The nanocomposite hydrogel material prepared by the present invention has a dynamic polymer network structure composed of a large number of reversible interactions such as hydrogen bonds, dynamic borate bonds or dynamic imine bonds, so it has both good mechanical strength and reliable self-repairing performance. At the same time, there are abundant free groups on the polymer chain of the nanocomposite hydrogel material prepared by the present invention, which makes it have self-adhesive properties and can be directly adhered to the surface of a matrix material such as the skin without the need for additional adhesives or fixing devices.
[0028] 2. The present invention constructs a flexible wearable sensor assembled from self-repairing and self-adhesive nanocomposite hydrogel materials based on reversible interactions. The incorporation of conductive nanofillers in the system effectively improves the mechanical strength, conductivity and sensing performance of the nanocomposite hydrogel, so that the assembled flexible wearable sensor has a broad application prospect in human motion signal and human electrophysiological signal monitoring, smart medical diagnosis, human-computer interaction perception, smart electronic skin, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 1 is the tensile stress-strain curve of the nanocomposite hydrogel material obtained in Examples 1 to 5.
[0030] Figure 2 1 is the tensile stress-strain curve of the nanocomposite hydrogel material obtained in Example 1 before and after self-repair.
[0031] Figure 3 It is the adhesion strength of the nanocomposite hydrogel material obtained in Example 1 to different materials after 5 cycles of adhesion.
[0032] Figure 4a ~d is the sensing response of the flexible wearable sensor assembled with the nanocomposite hydrogel material obtained in Example 1 to the movement of different parts of the human body.
[0033] Figure 5 The electrocardiogram signals of the human body in various states are monitored by the flexible wearable sensor assembled with the nanocomposite hydrogel material obtained in Example 1.
[0034] Figure 6 The electromyographic signals of different muscle states monitored by the flexible wearable sensor assembled with the nanocomposite hydrogel material obtained in Example 1.
[0035] Figure 7 This is a simulated abdominal wound pressure signal monitored by a flexible wearable sensor assembled with the nanocomposite hydrogel material obtained in Example 7.
[0036] Figure 8 It is a simulated cervical pessary pressure signal borne by the uterus monitored by a flexible wearable sensor assembled with the nanocomposite hydrogel material obtained in Example 7.
[0037] Fig. 9 This is a simulated intracranial pressure signal monitored by a flexible wearable sensor assembled with the nanocomposite hydrogel material obtained in Example 7. DETAILED DESCRIPTION
[0038] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0039] The MXene nanosheet solution used in the present invention can be obtained by a common preparation method, which is as follows:
[0040] 1g of lithium fluoride was added to 20mL of hydrochloric acid solution (concentration of 9M). After the lithium fluoride was completely dissolved, 1g of Ti3AlC2 powder was added to the above acidic etching solution. After stirring at 35°C for 24h, deionized water was repeatedly added for multiple centrifugation until the pH value of the upper clear liquid reached 6. The bottom precipitate was collected and freeze-dried at -30°C to obtain multi-layer MXene. A certain amount of multi-layer MXene powder was evenly distributed in deionized water by shaking, ultrasonically dispersed under inert gas protection for 1h, and finally centrifuged to obtain a stable upper monolayer solution with a MXene particle size of 200nm to 800nm.
[0041] Unless otherwise specified, other raw materials used in the embodiments and comparative examples are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation method disclosed in the prior art.
[0042] Example 1
[0043] Preparation of self-healing and self-adhesive nanocomposite hydrogel material OChS-Borax / Gelatin / MXene based on reversible interaction:
[0044] Step 1: Prepare 4 mg / mL MXene nanosheet solution.
[0045] Step 2: First, 10g of chondroitin sulfate (ChS) was uniformly dissolved in 100mL of deionized water, and 3.84g of sodium periodate (NaIO4) was uniformly dissolved in deionized water, and then added dropwise to the ChS solution at 4°C in the dark. After stirring for 12 hours, 4mL of ethylene glycol was added and stirred for 1 hour. Then, 7.626g of borax powder was added to 50mL of deionized water, and the above solution was added after stirring. After continuing to stir for 2 hours, the solution was poured into a dialysis bag and dialyzed with deionized water at room temperature for 3 days. Finally, the dialysate was freeze-dried to obtain borax-crosslinked aldehyde-modified chondroitin sulfate (OChS-Borax).
[0046] Step 3: Dissolve 0.25g of OChS-Borax in 0.5mL of MXene solution; at the same time, dissolve 0.25g of gelatin particles in 0.5mL of MXene solution at 50°C; mix the two solutions, stir them evenly, and let them stand at 37°C for 3-5min to form OChS-Borax / Gelatin / MXene hydrogel.
[0047] Example 2
[0048] The preparation process of the self-repairing self-adhesive nanocomposite hydrogel material is the same as that of Example 1, except that the mass ratio of OChS-Borax to Gelatin is 0.6:1, and specifically 0.15 g of OChS-Borax and 0.25 g of gelatin are used.
[0049] Example 3
[0050] The preparation process of the self-repairing self-adhesive nanocomposite hydrogel material is the same as that of Example 1, except that the mass ratio of OChS-Borax to Gelatin is 0.8:1, and specifically 0.2 g of OChS-Borax and 0.25 g of gelatin are used.
[0051] Example 4
[0052] The preparation process of the self-repairing self-adhesive nanocomposite hydrogel material is the same as that in Example 1, except that the mass ratio of OChS-Borax to Gelatin is 1.2:1, and specifically 0.3 g of OChS-Borax and 0.25 g of gelatin are used.
[0053] Example 5
[0054] The preparation process of the self-repairing self-adhesive nanocomposite hydrogel material is the same as that in Example 1, except that the mass ratio of OChS-Borax to Gelatin is 1.4:1, and specifically 0.35 g of OChS-Borax and 0.25 g of gelatin are used.
[0055] Example 6
[0056] Preparation of self-healing and self-adhesive nanocomposite hydrogel material Alg-PBA / PAAm / MXene based on reversible interaction:
[0057] Step 1: Prepare 3 mg / mL MXene nanosheet solution.
[0058] Step 2: Dissolve 1 g of sodium alginate (Alg) evenly in 200 mL of deionized water, add 0.98 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl) and 0.49 g of 3-aminophenylboronic acid, stir and react at room temperature for 24 hours, then pour the solution into a dialysis bag (3500 Da), and dialyze with deionized water for 7 days; freeze-dry the dialyzed solution at -80°C to obtain Alg-PBA powder.
[0059] Step 3: Dissolve 0.07 g of sodium alginate Alg-PBA grafted with phenylboronic acid, 1 g of acrylamide (PAAm), and 0.03 g of tannic acid (TA) in 6 mL of MXene nanosheet solution and stir thoroughly; then add 36 μL of azobisisobutylimidazoline hydrochloride initiator (AIBI, 0.125 g / mL) and 24 μL of 6,6'-diamino-3,3'-methylenedibenzoic acid crosslinker (MBAA, 0.1 g / mL), and add 0.1 M NaOH solution dropwise while stirring thoroughly to obtain Alg-PBA / PAAm / MXene hydrogel at 60 °C.
[0060] Example 7
[0061] Preparation of self-healing and self-adhesive nanocomposite hydrogel material PBA-HA / PVA / MXene based on reversible interaction:
[0062] Step 1: Prepare 6 mg / mL MXene nanosheet solution.
[0063] Step 2: First, 3.84g of sodium hyaluronate (molecular weight ~220000) was dissolved in 400mL of deionized water under stirring at room temperature. Secondly, 2.30g of EDC·HCl and 1.38g of NHS were dissolved in 400mL of dimethyl sulfoxide (DMSO) under stirring at room temperature. Then the two solutions were fully mixed under rapid stirring, and 1.096g of 3-aminophenylboronic acid was added to 200mL of deionized water, and after complete dissolution, it was added to the above mixed solution for grafting reaction, and the reaction lasted for 24h under stirring at room temperature. Finally, the obtained reaction product was poured into a dialysis bag (3500Da) and dialyzed in deionized water for 3 days, and HA-PBA was obtained after freeze-drying.
[0064] Step 3: Dissolve 0.04 g HA-PBA in 1 mL of a pre-prepared 6 mg / mL MXene uniform aqueous dispersion under manual stirring, then add 50 μL of Tris-HCl buffer to adjust the solution pH to a weak alkaline (greater than 8). Finally, add 1 mL of PVA solution (10 wt%) to the above solution, and PBA-HA / PVA / MXene hydrogel can be quickly formed after stirring.
[0065] Example 8
[0066] Preparation of self-healing and self-adhesive nanocomposite hydrogel material Alg-PBA / CMCS / MXene based on reversible interaction:
[0067] Step 1: Prepare 3 mg / mL MXene nanosheet solution.
[0068] Step 2: Dissolve 1 g of sodium alginate (Alg) evenly in 200 mL of deionized water, add 0.98 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl) and 0.49 g of 3-aminophenylboronic acid, stir and react at room temperature for 24 hours, then pour the solution into a dialysis bag (3500 Da), and dialyze with deionized water for 7 days; freeze-dry the dialyzed solution at -80°C to obtain Alg-PBA powder.
[0069] Step 3: Add 0.08 g of Alg-PBA and 0.02 g of carboxymethyl chitosan (CMCS) to 1 mL of MXene nanosheet solution, add 50 μL of tea polyphenol solution (TP, 0.2 g / mL) while stirring thoroughly, and add 50 μL of Tris-HCl buffer dropwise to obtain Alg-PBA / CMCS / MXene hydrogel.
[0070] Comparative Example 1
[0071] The preparation process of the composite material is the same as that of Example 1, except that in step 2, borax powder cannot be introduced for grafting without modification, and the composite material finally obtained cannot form a hydrogel.
[0072] Test Example 1 Mechanical Properties Test
[0073] The composite hydrogel materials obtained in Examples 1 to 5 were subjected to stress-strain curve tests at room temperature using a universal testing machine (ESM303) at a stretching rate of 20 mm / min. The results are shown in FIG. Figure 1 . Figure 1 It means that when the amount of gelatin is fixed, the content of OChS-Borax can be continuously increased to obtain OChS-Borax / Gelatin hydrogel with higher mechanical strength. This is because the number of dynamic borate bonds and dynamic cross-linking imine bonds inside the hydrogel increases, which increases the overall cross-linking degree of the hydrogel, resulting in increased mechanical strength and Young's modulus and reduced elongation at break.
[0074] Figure 2 The tensile stress-strain curves of the composite hydrogel material obtained in Example 1 before and after self-repair were tested. By completely cutting the composite hydrogel sample and re-contacting it, it was found that the two cut hydrogel strips could self-repair to form strips of the same length as the original after re-contact, and the fracture strength of the strips after self-repair was about 80.73% of the original, which shows that the composite hydrogel material has excellent self-repairing properties.
[0075] Test Example 2 Adhesion Strength Test
[0076] Adhesion strength test: Fix the material to be tested (glass, rubber, plastic, metal and pigskin) on the upper and lower surfaces of the stretching mold, sandwich the hydrogel sample between the upper and lower layers of the material, and apply vertical tensile stress to the mold at room temperature using a universal testing machine (ESM303) until the hydrogel sample is separated from the material to be tested. The stretching speed is 20mm / min, the effective length and width of the sample are both 20mm, and each group of materials is tested 5 times. The adhesion strength of the composite hydrogel material to the test material is calculated based on the ratio of the maximum tensile stress to the adhesion area. Figure 3 The adhesion strength of the composite hydrogel material obtained in Example 1 to different materials after repeated adhesion for 5 times is shown, wherein the maximum adhesion strength is 40.08 kPa for rubber, 56.55 kPa for plastic, 44.99 kPa for glass, 70.90 kPa for metal and 38.28 kPa for pigskin. At the same time, during the 5-cycle adhesion process, the adhesion strength to the same material is basically stable. Based on the above test results, it can be seen that the composite hydrogel material exhibits reliable adhesion performance to a variety of organic, inorganic and biological materials, and can be repeatedly adhered for many times.
[0077] Test Example 3: Sensing Performance Test
[0078] Figure 4a ~d was measured by an electrochemical workstation, the test mode was it mode, the test voltage was 0.5V, and the sampling interval was 0.05s. Figure 4a The composite hydrogel material is attached to the wrist as a sensor. When the wrist is bent, the composite hydrogel material-based sensor forms good adhesion with the skin and undergoes tensile strain, generating a real-time sensor response signal. Keeping the bending action and angle unchanged, repeated bending can still obtain a sensor signal with a basically stable peak shape and peak value, showing that the sensor response signal obtained by the composite hydrogel material-based sensor to monitor large-scale human body movements has good stability and repeatability. Figure 4b The composite hydrogel material-based sensor adhered to the elbow joint can accurately collect the sensor response signals of the elbow joint at different bending angles, and the signal value increases with the increase of the bending angle, indicating that the sensor has the ability to accurately identify and distinguish the sensor response of different movement amplitudes of the human body. Figure 4c By applying the sensor to the radial artery pulse of the human body, it can accurately detect complete, continuous and repeatable pulse waveforms and characteristic peaks, such as characteristic systolic peak (P1) and diastolic peak (P2). Important parameters can be calculated based on the peak values, such as: P2 / P1 is defined as the radial artery enhancement index (AIr), which is often used in the clinical diagnosis of cardiovascular diseases, such as arteriosclerosis, arterial wall damage, etc. Figure 4d As shown in the figure, the hydrogel was attached to the neck of the volunteer to detect the jugular vein pulse signal in real time, and the jugular vein pulse frequency was observed to be 80 times / minute; at the same time, the typical jugular vein pulse (JVP) characteristic peaks can be observed, including atrial contraction peak (A), tricuspid valve bulging peak (C), atrial relaxation peak (X), atrial systolic filling peak (V) and ventricular early filling peak (Y). The use of hydrogel sensors for real-time detection of human jugular vein pulse signals provides a new path for remote medical diagnosis of various cardiovascular diseases (such as arteriosclerosis and heart failure), indicating the great application prospects of this multifunctional sensor in the field of intelligent human health monitoring.
[0079] Figure 5 The ECG signals of volunteers in different motion states were sampled and recorded by a wireless ECG recorder (ER1) at a sampling frequency of 1000Hz. When the composite hydrogel material is combined with the wireless ECG recorder, the composite hydrogel material-based sensor integrated in the wireless ECG recorder component can be adhered to the chest of the volunteer to perform wireless monitoring of ECG signals. Figure 5As shown in the figure, the composite hydrogel sensor and commercial electrodes were used to test the heart rate of volunteers in an active state. It can be seen that as the intensity of exercise increases, the heart rate of the volunteers increases. Although the ECG signal monitored by the composite hydrogel material sensor during running has slight jitters, it remains stable as a whole without obvious drift, and the complete P, Q, R, S, and T waveforms can be clearly identified. However, due to the poor adhesion and low sensing performance of commercial electrodes, it is impossible to obtain stable and effective ECG signals when the human body is in motion.
[0080] Figure 6 The biosignal acquisition and analysis system collects and analyzes the volunteers' electromyographic signals at a sampling frequency of 5000 Hz. The MXene nanocomposite hydrogel is attached to the volunteers' left and right forearms as electrodes. Figure 6 It shows that MXene nanocomposite hydrogel can monitor the changes in electromyographic signals when the human arm muscles are clenched in real time, and the EMG signals from healthy muscles detected by MXene nanocomposite hydrogel are stronger and clearer than the EMG signals from atrophied muscles. By identifying the strength of electromyographic signals, it is possible to indicate the health status and fatigue level of muscles, which is of great significance for the diagnosis of sarcopenia in the elderly and rehabilitation training of muscle strength.
[0081] Figure 7-Figure 9 All were measured by an electrochemical workstation, the test mode was it mode, the test voltage was 0.5V, and the sampling interval was 0.05s. Figure 7 It is a simulated abdominal wound pressure signal monitored by a flexible wearable sensor assembled from MXene nanocomposite hydrogel materials. Figure 7 As shown, PBS solution (simulated body fluid) is loaded into a balloon to simulate the pressurized abdominal cavity, MXene nanocomposite hydrogel is adhered to the damaged part of the balloon, and the balloon is continuously squeezed to simulate the real-time movement of the traumatic abdominal cavity. It can be seen that the MXene nanocomposite hydrogel sensor can test the pressure signal in real time, proving that MXene nanocomposite hydrogel has great potential in temporarily closing the abdominal cavity, timely and rapid hemostasis, and real-time monitoring of abdominal cavity pressure. It can be seen that the self-repairing and self-adhesive MXene nanocomposite hydrogel provided by the present invention can be used for both hemostatic dressings and pressure monitoring of the battle-damaged abdominal cavity, and can be used to apply to the diverse war injuries in today's wars.
[0082] Figure 8 The simulated cervical pessary pressure signal under the uterus is monitored by a flexible wearable sensor assembled from MXene nanocomposite hydrogel materials. Figure 8As shown, a balloon filled with PBS solution is used to simulate the uterus, and a MXene nanocomposite hydrogel sensor is attached to the surface of the cervical pessary. The balloon is placed on the upper part of the cervical pessary, and the balloon is continuously squeezed to simulate the uterine contraction process, so that the pressure signal can be collected in real time, indicating the possibility of integrating MXene nanocomposite hydrogel into a cervical pessary for monitoring cervical pressure during pregnancy. While the cervical pessary supports the cervix and improves the force on the uterus, it can also monitor the cervical pressure in real time, thereby detecting the cervical pressure of pregnant women in different stages of labor, which has a certain auxiliary significance for doctors to diagnose and regulate the condition of pregnant women.
[0083] Fig. 9 It is a simulated intracranial pressure signal monitored by a flexible wearable sensor assembled from MXene nanocomposite hydrogel materials. Fig. 9 As shown in the figure, the MXene nanocomposite hydrogel sensor is attached to a balloon filled with PBS solution, and the intracranial pressure generated by cerebrospinal fluid on the inner skull is simulated by continuous squeezing of the balloon, and a stable pressure sensing signal can be monitored. This provides a new idea for the application of MXene nanocomposite hydrogel sensors in a new generation of non-invasive and accurate intracranial pressure monitoring methods.
[0084] The above experimental results prove that the self-healing and self-adhesive composite hydrogel material provided by the present invention can be used as a flexible wearable sensor to realize sensitive and stable multi-scale human motion monitoring and high-quality acquisition of human electrophysiological signals, showing broad application prospects in personal health monitoring, remote medical diagnosis and postoperative rehabilitation training.
Claims
1. A self-repairing and self-adhesive nanocomposite hydrogel material, comprising a mixture and / or a reaction product of a first monomer modified by a boric acid derivative, a second monomer, and a conductive filler.
2. The self-repairing self-adhesive nanocomposite hydrogel material according to claim 1, characterized in that: The first monomer in the boric acid derivative modified first monomer is selected from at least one of sodium alginate, chondroitin sulfate, sodium hyaluronate, carboxymethyl cellulose and glycyrrhizic acid; and / or, The boric acid derivative in the first monomer modified by the boric acid derivative is selected from at least one of inorganic boric acid derivatives and organic boric acid derivatives, preferably at least one of borax, boric acid, 3-aminophenylboronic acid and 3-carboxyphenylboronic acid; and / or, The second monomer is selected from at least one of acrylamide, dopamine, chitosan, carboxymethyl chitosan, gelatin, guar gum, and polyvinyl alcohol; and / or, The conductive filler is selected from at least one of MXene, carbon black, carbon nanotubes, graphene, reduced graphene oxide, molybdenum disulfide, tungsten disulfide, black phosphorus, liquid metal particles, metal nanoparticles, conductive graphite, and silver nanowires; and / or, The particle size of the conductive filler is 1 nm to 150 μm, preferably 50 nm to 3 μm.
3. The self-repairing and self-adhesive nanocomposite hydrogel material according to claim 1, characterized in that: Taking the total mass of the first monomer, the second monomer and the conductive filler modified by the boric acid derivative as 100%, the first monomer modified by the boric acid derivative is 1-85%, the second monomer is 15-98%, and the conductive filler is 0.1-10%; preferably, taking the total mass of the first monomer, the second monomer and the conductive filler modified by the boric acid derivative as 100%, the first monomer modified by the boric acid derivative is 3-75%, the second monomer is 20-93%, and the conductive filler is 0.3-8%.
4. A method for preparing the self-repairing self-adhesive nanocomposite hydrogel material according to any one of claims 1 to 3, comprising: The components including the first monomer modified by the boric acid derivative, the second monomer and the conductive filler are mixed, and the self-repairing and self-adhesive nano composite hydrogel material is obtained after reaction.
5. The preparation method according to claim 4, characterized in that: The preparation method specifically comprises the following steps: Step 1, preparing a dispersion of a conductive filler; Step 2, adding a boric acid derivative and a reaction additive to the aqueous solution of the first monomer, stirring and reacting, to obtain a first monomer modified with a boric acid derivative; Step 3: Mix the first monomer modified by the boric acid derivative, the second monomer and the conductive filler dispersion, and stir to react to obtain the self-repairing and self-adhesive nanocomposite hydrogel material.
6. The preparation method according to claim 5, characterized in that: In the step 1: The solvent in the dispersion of the conductive filler is water; and / or, The concentration of the conductive filler dispersion is 1 to 10 mg / mL, preferably 3 to 6 mg / mL.
7. The preparation method according to claim 5, characterized in that: In the step 2: The concentration of the first monomer aqueous solution is 0.01 to 45 wt%, preferably 0.5 to 30 wt%; and / or, The reaction additive is selected from at least one of sodium periodate, ethylene glycol, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and N-hydroxysuccinimide; and / or, The mass ratio of the first monomer, the boric acid derivative and the reaction additive is 1:(0.1-1):(0.2-2), preferably 1:(0.2-0.8):(0.3-1.5); and / or, The reaction conditions are 0-40° C. for 0.5-72 h, preferably 4-35° C. for 4-48 h.
8. The preparation method according to claim 5, characterized in that: The step three comprises the following steps: The first monomer and the second monomer modified by the boric acid derivative are added to the conductive filler dispersion respectively, and stirred sufficiently for reaction to obtain the self-repairing self-adhesive nanocomposite hydrogel material; or, The first monomer and the second monomer modified by the boric acid derivative are sequentially added to the conductive filler dispersion, and an initiator and a cross-linking agent are optionally added, and the mixture is fully stirred for reaction to obtain the self-repairing and self-adhesive nanocomposite hydrogel material.
9. The preparation method according to claim 8, characterized in that: The initiator is selected from at least one of peroxide initiators and azo initiators, preferably at least one of azobisisobutylimidazoline hydrochloride, ammonium persulfate, potassium persulfate, and benzoyl peroxide; and / or, The cross-linking agent is selected from at least one of 6,6'-bisamino-3,3'-methylene dibenzoic acid cross-linking agent, N,N'-methylenebisacrylamide, tannic acid, tea polyphenols, Tris-HCl buffer solution and NaOH.
10. Use of the self-repairing self-adhesive nanocomposite hydrogel material according to any one of claims 1 to 3 or the self-repairing self-adhesive nanocomposite hydrogel material obtained by the preparation method according to any one of claims 4 to 9 in flexible wearable sensors and pressure detection sensors.
Citation Information
Patent Citations
High-elasticity hydrogel sensor and preparation method thereof
CN114149595A
Rapid self-healing conductive hydrogel sensor and preparation method thereof
CN114854047A
Medical hydrogel with pH sensitivity, self-healing nature and cell adhesion and preparation method thereof
CN108530651A
Anti-freezing self-repairing conductive hydrogel and preparation method thereof and flexible sensor
CN112608508A
MXene hydrogel used for sensing signal detection and having high mechanical strength and degradation recycling performance and preparation method thereof
CN115873269A
Cited By
MXene-based ammonium glycyrrhizinate / konjac glucomannan / borax self-repairing hydrogel and preparation method thereof
CN120173149A
MXene-based ammonium glycyrrhizinate / konjac gum / borax self-repairing hydrogel and preparation method thereof
CN120173149B
Preparation method and application of Janus structure photo-thermal-piezoelectric hydrogel dressing for infected wound repair
CN120733112A
Ferulic acid-mediated high-adhesion hydrogel composition, hydrogel as well as preparation method and application of ferulic acid-mediated high-adhesion hydrogel composition
CN122103426A